FACTORS EFFECTTING ON FAILURE AT CARDAN COUPLINGS AND PRECAUTIONS WHICH MUST BE TAKEN - Mehmet UÇAR (Pamukkale University Journal of Engineering Sciences, 1999)
In this study, failures caused by bad usage during operation and by manufacturing are examined. Failures occurred on cardan coupling are analyzed by using of photographs which have been taken. As not to be occurred any failures on cardan coupling before its usage life, it has been seen that system must not be over loaded, exact oiling in areas which have relative motion must be used, oil used must have high performance at both low and high temperature (- 30 o C, 120 o C), cross pin and needle bearing must have high strength against to wear and shock loads, internal strength on the areas which have been connected by welding must be decreased and coupling must be balanced as statically and dynamic.